Bromo as the body of God: Savanna Blazes and Yadnya Kasada ethnobotany in the perspective of Pentecostal eco-pneumatology - Afandi, Yahya (KURIOS, 2024)
This study is a response to growing concern about the accumulation of ecological crises and other troubling bio-geological changes that have occurred recently on both a global and local scale. However, this conversation will be restricted to a local scale due to numerous constraints, particularly responding to the ecological tragedy of forest and land fires in the Bromo savanna in early September 2023. The thesis of this paper is that â€œBromo as the body of Godâ€ can be an imaginative critique of a forest and land fire incident involving one of the Tengger tribe's local wisdom of nature conservation known as the ethnobotany of the Yadnya Kasada ceremony and studied from the standpoint of Pentecostal Eco-pneumatology. To demonstrate this argument, I utilized a descriptive-analysis approach based chiefly on the works of a feminist eco-theologian named Sallie McFague, which was then interlaced with sharp insights from some Pentecostal/Charismatic (P/C) scholars. As a result, the metaphor of â€œBromo as the Body of Godâ€ proposes a new ecological paradigm that simultaneously unites human tears, earth tears, and God's tears. The sacred character of the earth as a manifestation of His body must compel efforts to manage, restore, and maintain the Bromo Tengger Semeru National Park (Taman Nasional Bromo Tengger Semeru, TNBTS) region as a tangible representation of the need to care for the sustainability of the current environment.